2008
DOI: 10.1186/1757-1626-1-49
|View full text |Cite
|
Sign up to set email alerts
|

Adrenalectomy for solitary adrenal metastasis from colorectal cancer: A case report

Abstract: Background: Patients with adrenal metastasis from various primary tumours are regarded as cases of diffuse systemic spread and considered unsuitable for surgical resection. We herein report an operable case of heterochronic adrenal metastasis from colorectal carcinoma in a 63-year-old woman.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…As the patient had a history of colon cancer, we first presumed that the BM and AM originated from the colon. However, BM and AM from colon cancer are relatively rare, and the staining pattern of previous colon cancer was inconsistent with that of the adrenal tumor [9][10][11]. Thus, we concluded that the metastasis was not from the colon.…”
Section: Discussionmentioning
confidence: 77%
“…As the patient had a history of colon cancer, we first presumed that the BM and AM originated from the colon. However, BM and AM from colon cancer are relatively rare, and the staining pattern of previous colon cancer was inconsistent with that of the adrenal tumor [9][10][11]. Thus, we concluded that the metastasis was not from the colon.…”
Section: Discussionmentioning
confidence: 77%
“…By contrast, a solitary adrenal metastasis is extremely unusual. When a solitary adrenal metastasis is observed, surgical resection of the involved adrenal glands is associated with a good prognosis for patients ( 1 , 2 , 4 7 , 12 16 , 35 37 ). Muth et al reported that the factors associated with a longer survival time in patients with CRC, renal cell carcinoma, non-small-cell lung cancer and malignant melanoma were the tumor type, of which CRC demonstrated the best prognosis, no prior surgery or metastases, a long disease-free interval and potentially curative adrenalectomy at the time of surgery ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the liver and the lung are the main metastatic sites of CRC, the adrenal metastasis is clinically rare. But in autopsy series, the metastasis ranges are from 1.9% to 17.4 [1,9]. The rate of detecting clinically silent adrenal masses has increased due to the widespread use of abdominal imaging modalities, including USG, PET-CT, MRI [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…To identify the adrenal mass is either malign or benign biopsy should be performed. In autopsy studies, the prevalence of incidentaloma is 1-9% [13] and the rate of metastasis ranges from 1.9-17.4% [1,9]. It is generally accepted that a solitary adrenal metastasis should be resected immediately to achieve good prognosis in some cancer types [14][15].…”
Section: Discussionmentioning
confidence: 99%